Review of the Literature on Smart Grid Cybersecurity (International Journal of Innovative Research in Computer Science & Technology, 2021)
The existing power generation grid with in  United States seems to be an antiquated architecture, and  the Home Automation is an overhaul that will contain a  new features to fit customers' evolving power demands.  Updating a systematic approach like the electricity  network has the ability to bring new security  vulnerabilities. This article gives an outline of the efforts  undertaken in the field of Renewable Energy cyber  security. Controller (PCS) Risk, Proposed Smart Stability,  Electric Grid Model Based Security, Distributed  Generation Data Link Protection, and Smart Grid  Simulations for Security Research are really the areas that  make up various pieces of the Smart Grid. The Power  System is a vast, intricate infrastructure that still needs  substantial cyber defense preparation.
Keywords: Cyber-Attacks; Cyber Security; Cyber Threat; Power Grid; Smart Grid